Analisis dan Perancangan Desain Sistem Informasi Pembayaran Tagihan Supplier Pada PT. Jaya Teknik Indonesia Berdasarkan Kebutuhan Sistem - Tri Hariyadi; Dewi Laraswati; Fattya Ariani (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Economic development in Indonesia is currently growing rapidly. To achieve this economic development, a good system is needed. One of these systems is a payment system. That is a system that deals with payments made by a company to suppliers so that a job can be completed on time without any financial disturbances. An integrated system makes it easy for employees to do their work. PT Jaya Teknik Indonesia is a contracting company. The existing system of PT Jaya Teknik Indonesia is currently not computerized. The manual process for checking the billing file causes the length of the payment process due to the large number of billing files that have to be processed and not connected between one part and another so that to conduct a complete data check must ask directly the relevant part. Because of this, the author tries to make the bill payment system of suppliers at PT Jaya Teknik Indonesia. This payment system analysis is made to solve the problems that exist in this company in order to achieve an effective and efficient system in carrying out activities in the company. Keywords: System Design, Payment Information System Design, Payment Information System, Bill Payment Information System